2014
DOI: 10.1002/dc.23093
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of ancillary studies in the cytologic diagnosis of biliary and pancreatic lesions: The papanicolaou society of cytopathology guidelines for pancreatobiliary cytology

Abstract: The Papanicolaou Society of Cytopathology has developed a set of guidelines for pancreatobiliary cytology including indications for endoscopic ultrasound-guided fine-needle aspiration, terminology and nomenclature of pancreatobiliary disease, ancillary testing, and post-biopsy management. All documents are based on the expertise of the authors, a review of the literature, discussions of the draft document at several national and international meetings, and synthesis of selected online comments of the draft doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 100 publications
3
77
0
Order By: Relevance
“…Similar findings were observed in Asian populations in several small-cohort studies [16, 17]. In summary, UroVysion FISH appears to improve diagnostic sensitivity [4, 5, 13]. The sensitivity of routine cytology in the studies with corresponding FISH assays appears to be lower than that reported in studies with routine cytology alone (Table 4) [11].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Similar findings were observed in Asian populations in several small-cohort studies [16, 17]. In summary, UroVysion FISH appears to improve diagnostic sensitivity [4, 5, 13]. The sensitivity of routine cytology in the studies with corresponding FISH assays appears to be lower than that reported in studies with routine cytology alone (Table 4) [11].…”
Section: Discussionmentioning
confidence: 50%
“…The UroVysion FISH assay is considered as diagnostically useful, and is the preferred test to complement routine cytology to aid in the detection of malignant pancreatobiliary strictures by the Papanicolaou Society of Cytopathology [4]. However, the possibility of false-positive FISH results should always be considered, and may limit the utility of FISH in the diagnosis of malignancy in bile duct brushing specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCAs are reported to express inhibin, calponin, and somatostatin receptors -all of which can be identified using immunohistochemical staining. Although a small number of studies have found that this improves the diagnostic accuracy of cytology for SCAs [19][20][21] , in this study an adequate cyst lining was only found in 10% of smears with SCAs. Furthermore, immunostaining needs cell block preparation which may or may not have adequate cellularity for further evaluation, suggesting the utility of immunohistochemistry may be limited.…”
Section: Discussionmentioning
confidence: 57%
“…The "string sign," a marker of viscosity, is performed by placing fluid between the thumb and index finger and gently pulling apart. If the fluid stretches out to at least 3.5 mm, this is consistent with a mucinous cyst [61]. SCAs typically have thin, serosanguinous or frankly bloody fluid.…”
Section: How Can Eus-fna Aid In Diagnosis?mentioning
confidence: 91%